IDENTIFICATION OF RISK FACTORS ASSOCIATED WITH THE INCIDENCE DIABETES MELLITUS IN ADOLESCENTS: A REVIEW - Kusumajaya, Ida; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT The International Diabetes Federation (IDF) predicts that at least 463 million people suffer from diabetes worldwide in 2019, equivalent to 9.3% of the population in the same age group. The Indonesian Pediatrician Association, stated that along with the increasing number of obesity among adolescents, the incidence of various obesity complications, such as type-2 diabetes, also increased. The increase in the incidence of diabetes mellitus in adolescents is associated with changes in social status and following modern lifestyles, such as lack of physical activity (exercise) and unhealthy eating habits, which results in obesity and can cause insulin resistance to lead to Diabetes Mellitus. This study is a literature review with the aim of identifying factors that increase the risk of diabetes in adolescence. Searching for publication articles is done with Google Scholar and Pubmed databases using the search terms diabetes mellitus, risk factors, adolescents. Research Methodology is carried out by searching, collecting, reviewing and analyzing research articles that meet the requirements that have been set. The results of the article analysis are then used to make a literature review review. Based on a review of several research articles that have been analyzed, it was concluded that in this study showed a relationship between premature birth, physical activity, diet, smoking and obesity with risk factors for diabetes in adolescents. Suggestion: it is expected that the involvement of various parties in efforts to prevent the increasing prevalence of diabetes mellitus. Keywords: Adolescent Children, Diabetes Mellitus, Risk Factors